Comprehensive Analysis of Storage Stability of Hong-Jam Under Various Conditions: Correlation Between Lipid Oxidation Factors and Alternative Quality Parameters - Min-Seok Kim; Sang-Jin Ye; Ji-Hwan Roh; Hyun-Wook Choi; Moo-Yeol Baik (Foods)
Hong-Jam is a functional food product made from freeze-dried silkworms on the seventh to eights day of the fifth Instar stage, which are steamed for 2 h prior to drying. This study evaluated the storage stability of Hong-Jam under varying temperatures, product forms, and packaging conditions. By using the correlation analysis, novel quality indices that may complement or replace traditional lipid-oxidation markers in edible-insect products were identified. Peroxide value (POV) and acid value (AV), which are factors of lipid oxidation, significantly increased under high-temperature conditions. Dependency of temperature (DT) analysis revealed that POV had a higher DT than AV, and glass bottles exhibited higher DT than polyethylene (PE) pouches. In the four-way analysis of variance (ANOVA) analysis, the Fisher’s F-statistic (F-value) for single effects of individual storage conditions was notably higher than the interaction effects. During storage, the moisture content increased and the pH decreased, while the color remained relatively stable. The results of the correlation analysis indicated that there was a significant correlation between moisture content and pH with lipid oxidation indices such as POV and AV. This suggests that these two factors could be used as complementary factors in quality assessments. In conclusion, this research provides foundational data that can be used to develop improved storage standards and quality assurance protocols for Hong-Jam and similar edible insect foods. These advancements will contribute to extending shelf life, enhancing consumer safety, and promoting the broader acceptance of edible insects in the food industry. Through a comprehensive understanding of the stability factors, this study supports the development of reliable quality management practices that align with the increasing consumer demand for sustainable and functional food options.